STATISTICAL AND SEMANTIC METHODS OF ANALYZING TRENDS IN PRODUCTION, TRANSPORTATION AND THE USE OF COAL-WATER FUEL - V.R. Roganov; V.V. Shvyrov (Надежность и качество сложных систем, 2024)
Background. The increase in the number of publications on the production and use of coal-water suspensions is due to the global increase in energy consumption, rising energy prices, as well as the needs to expand the fuel base in modern energy. On the other hand, interest in this area is associated with the issues of disposal of accumulated coal waste. In this regard, the task of systematizing and classifying the approaches proposed by various authors in the field of effective use of coal-water suspensions and coal-water fuel becomes urgent. Materials and methods. This paper presents an analysis of publications using modern methods of statistical and semantic analysis of big data. Results and conclusions. In particular, based on frequency analysis data, latent trends in the field of research related to coal-water fuel have been identified, methods for recycling water-coal fuel, and factors that determine the rheological properties of water-coal fuel have been identified. In addition, a classification of studies by type of coal was made.